\(\frac{\left(-3\right)^{10}.15^5}{25^3.\left(-9\right)^7}\)
giúp mình với
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Có: \(\dfrac{\left(-3\right)^{10}x15^5}{25^3x\left(-9\right)^7}=\dfrac{3^{10}.\left(3.5\right)^5x}{-\left(3^2\right)^7\left(5^2\right)^3x}\)
\(=\dfrac{3^{15}.5^5x}{-3^{14}.5^6x}\)\(=\dfrac{3^{14}.5^5\left(3x\right)}{3^{14}.5^5\left(-5x\right)}=\dfrac{3x}{-5x}=-\dfrac{3}{5}\)
Vậy...
A) \(\frac{1}{2}\cdot\left(\frac{2}{9}+\frac{3}{7}-\frac{5}{27}\right)\)
\(=\frac{1}{2}\cdot\frac{1}{2}\)
\(=\frac{1}{4}\)
B) \(\left(\frac{-5}{28}+1.75+\frac{8}{35}\right):\left(-3\frac{9}{20}\right)\)
\(=\left(\frac{-5}{28}+\frac{7}{4}+\frac{8}{35}\right):\frac{-69}{20}\)
\(=\frac{14}{5}:\frac{-69}{20}\)
\(=\frac{-56}{69}\)
a) \(\frac{\left(17\frac{2}{9}-15\frac{2}{15}\right):5\frac{2}{9}}{\left(18+3,75\right):0,25}.25\%=\frac{\left(17+\frac{2}{9}-15-\frac{2}{15}\right):\frac{47}{9}}{\left(18+3,75\right).4}.\frac{1}{4}\)
\(=\frac{\left(2+\frac{4}{45}\right).\frac{9}{47}}{\left(18+3,75\right).16}=\frac{\frac{94}{45}.\frac{9}{47}}{288+60}=\frac{\frac{2}{5}}{348}=\frac{2}{5}.\frac{1}{348}=\frac{174}{5}=34,8\)
b) \(\frac{\frac{5}{3}-\frac{5}{7}+\frac{5}{9}}{\frac{10}{3}-\frac{10}{7}+\frac{10}{9}}=\frac{5\left(\frac{1}{3}-\frac{1}{7}+\frac{1}{9}\right)}{10\left(\frac{1}{3}-\frac{1}{7}+\frac{1}{9}\right)}=\frac{1}{2}\)
b) \(\frac{\frac{5}{3}-\frac{5}{7}+\frac{5}{9}}{\frac{10}{3}-\frac{10}{7}+\frac{10}{9}}=\frac{5.\left(\frac{1}{3}-\frac{1}{7}+\frac{1}{9}\right)}{10.\left(\frac{1}{3}-\frac{1}{7}+\frac{1}{9}\right)}=\frac{5}{10}=\frac{1}{2}\)
\(a)\frac{(-5)^{60}.30^5}{15^5.5^{61}}=\frac{(5.2.3)^5}{(5.3)^5.5}=\frac{5^5.2^5.3^5}{5^5.3^5.5} =\frac{2^5}{5}=\frac{32}{5}\)
\(b) \frac{(-3)^{10}.15^5}{25^3.(-9)^7}=\frac{(-3)^{10} .(3.5)^5}{(5^2)^3.[(-3).3]^7}=\frac{(-3)^{10}.3^5.5^5}{5^6.(-3)^7.3^7}=\frac{(-3)^3}{5.3^2}=\frac{-3}{5}\)
~ Hok tốt a~
bài 1)
a) \(\dfrac{\left(-3\right)^{10}.15^5}{25^3.\left(-9\right)^7}\)
\(=\dfrac{\left(-3\right)^{10}.\left(3.5\right)^5}{\left(5^2\right)^3.\left(-3.3\right)^7}\)
\(=\dfrac{\left(-3\right)^{10}.3^5.5^5}{5^6.\left(-3\right)^7.3^7}\)
\(=\dfrac{\left(-3\right)^3.1.1}{5.1.3^2}\)
\(=\dfrac{-27.1.1}{5.1.9}\)
\(=\dfrac{-27}{45}\)
\(=\dfrac{-9}{15}\)
b)\(2^3+3.\left(\dfrac{1}{9}\right)^0-2^{-2}.4\left[\left(-2\right)^2:\dfrac{1}{2}\right].8\)
\(=8+3.1-\dfrac{1}{2^2}.4+\left[\left(4:\dfrac{1}{2}\right)\right].8\)
\(=8+3.1-\dfrac{1}{4}.4+\left[4.\dfrac{2}{1}\right].8\)
\(=8+3.1-\dfrac{1}{4}.4+8.8\)
\(=8+3-1+64\)
\(=11-1+64\)
\(=10+64\)
\(=74\)
(-3)^10.15^5/25^3.(-9)^7 = 3^10.3^5.5^5/5^6.3^14.(-1) = 3^15.5^5/5^6.3^14.(-1)= 3/5(-1) = -3/5